PENERAPAN MODEL CIPP DALAM EVALUASI PROGRAM SRA PADA MIN 27 ACEH SELATAN - Mutia, Sri (Universitas Islam Negeri Sumatera Utara Medan, 2024)
This article is the result of a study that discusses the application of the CIPP model in the evaluation of the SRA program at MIN 27 South Aceh. This qualitative study uses a qualitative research method by emphasizing the naturalistic results of the research results showing that: The application of the CIPP model in the evaluation of the SRA program at MIN 27 South Aceh can be seen from the evaluation of the context, input, product and process where, the context model in the SRA program is: Character formation as a child-friendly school culture that equips students to be able to actualize their personality towards Islamic character, while the input is the honesty of the student's character which is equipped by teachers, parents and education personnel by always socializing about children's rights and child-friendly schools, the evaluation of the process is an interactive, inspiring, fun, challenging activity, motivating students to play an active role. where CCTV is installed in every corner of the canteen where every Saturday their extracurricular activities will watch their activities in the canteen honestly so that students are more responsive and the evaluation of the product is students where they are able to actualize their personality towards Islamic character by being honest even though not all of them are optimal but they have been accustomed to it since early on.